Military expenditure, security outcome and industrialisation in Africa: Evidence from a panel data analysis. Issue 2 (3rd April 2021) - Saba, Charles Shaaba; Ngepah, Nicholas
ABSTRACT: This study examines the cause-and-effect relationship between military expenditure, security outcome and industrialisation for a panel of 35 African countries spanning from 1990 to 2015. We employed: (i) the Pairwise Dumitrescu-Hurlin panel causality test; and (ii) the newly developed panel VAR in generalised method of moment (GMM) estimation approach was applied to determine what magnitude can future disparities in industrialisation be explained by military expenditure and security outcome. The empirical results suggest the existence of a long-run relationship between military expenditure, security outcome and industrialisation. The causality tests reveal that there is feedback causality between the three variables: Military expenditure promotes security outcome and industrialisation in Africa and vice versa. Thus, an appropriate defense and security sector policies will further contribute to the industrialisation process of Africa.